THE EFFECT OF VISION AND MISSION STATEMENT ON PERFORMANCE OF HOSPITAL IN ASIA : A SYSTEMATIC REVIEW - Pamungkas, Tegar; Muhammad Syafril Firdaus,; Permana Putra, Dwi; Srihartini Gultom, Lamtioma Roito; Rahmat, Arif; Gede Kumara Dipa, Ida Bagus; Karsontani, Rio; Veranita, Mira (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Few studies evaluate hospital mission, vision, and values. Just one reveals how hospital managers view their mission statements. According to study, the hospital's purpose, vision, and values stimulate employee dedication and improve staff performance and operational efficiency.  The aim: This study demonstrated the effect of vision and mission statement on performance of Hospital in Asia. Methods: Comparing itself to PRISMA 2020 standards showed that this study met all requirements. Therefore, the specialists were able to keep the study current. This search method considered 2010–2024 publications. This was done using Google Schoolar and other web sources. Review pieces, previously published works, and unfinished works were excluded. Result: In the Google Schoolar database, the results of our search brought up 512 articles. The results of the search conducted for the last year of 2010 yielded a total 162 articles. In the end, we compiled a total of 3 papers. Conclusion: There will be a connection between the organizational culture and the vision and mission of a health service providing agency. The level of performance that will be achieved as a result of this will be both effective and efficient.